Factors related to obesity and overweight among Black adolescent girls in the United States. Issue 2 (7th February 2017) - Winkler, Megan R.; Bennett, Gary G.; Brandon, Debra H.
ABSTRACT: In the United States, Black adolescents have the highest prevalence of pediatric obesity and overweight among girls. While Black girls are disproportionately affected, the reasons for this health disparity remain unclear. The authors conducted a systematic review to investigate the factors related to obesity and overweight among Black adolescent girls. The authors searched four databases for relevant English-language publications using all publication years through 2015. Fifty-one studies met the inclusion criteria and were used for this review. Using a configuration approach to synthesis, three categories were identified, paralleling the bioecological theory of human development: (1) individual, (2) interpersonal, and (3) community and societal factors. A description of each factor's association with obesity among Black adolescent girls is presented. From this review, the authors identified a diverse and vast set of individual, interpersonal, and community and societal factors explored for their relationship with obesity and overweight. Given the insufficient repetition and limited significant findings among most factors, the authors believe that multiple gaps in knowledge exist across all categories regarding the factors related to obesity and overweight among Black adolescent girls. To improve the quality of research in this area, suggested research directions and methodological recommendations are provided.